Multimodality imaging findings of visceral myopathy in a child presenting with palpable abdominal mass - (:unkn) unknown (TURKISH J PEDIATRICS, 2019)
Visceral myopathy is a rare cause of intestinal obstruction characterized by intestinal dysmotility and constipation. Patients often present with recurrent abdominal pain, vomiting and abdominal distension. We report a rare case of visceral myopathy in a child presenting with intraabdominal mass. We aimed to describe ultrasound, computed tomography and magnetic resonance enterography findings of this rare disease that has not been demonstrated before. Differential diagnosis of mural thickening with distinguishable layers in addition to intestinal dilatation in the absence of mesenteric inflammation includes visceral myopathy.
Keywords: visceral myopathy; intestinal obstruction; ultrasound; magnetic resonance imaging; computed tomography; CHRONIC INTESTINAL PSEUDOOBSTRUCTION; GASTROINTESTINAL-TRACT; SMALL-BOWEL; FEATURES; DOPPLER; DISEASE